Catalytic ozonation of dichloromethane at low temperature and even room temperature on Mn-loaded catalysts. Issue 51 (22nd November 2022) - Duan, Yaxin; Liu, Peixi; Lin, Fawei; He, Yong; Zhu, Yanqun; Wang, Zhihua
Abstract : The collaboration of abundant surface oxygen species and weak acid sites at low temperatures ensures the best functioning of M/A-II. Abstract : Five Mn-loaded catalysts were synthesized on γ-Al2 O3, TiO2, ZrO2, nano γ-Al2 O3 and nanoZrO2 supports. The catalytic ozonation of DCM (dichloromethane) was evaluated under industrial conditions ( i.e., temperature, O3 input, H2 O and SO2 content). According to results, >90% DCM conversion without O3 residue was achieved for all samples at 120 °C and an O3 /DCM ratio of 6. At 20–120 °C, the highest Mn 3+ content, abundant surface oxygen species and more weak acid sites led to the best performance of Mn/nanoAl2 O3 (M/A-II). At 20 °C and 120 °C, 80% and 95% DCM can be degraded respectively on M/A-II at 20 °C with matched surface oxygen species and acidity. An O3 /DCM ratio of 6 was optimal for performance and economy. For the effects of complex exhaust, both H2 O and SO2 deactivated M/A-II. The H2 O-induced deactivation was recoverable and also removed surface-deposited chlorine-containing species, enhancing the HCl selectivity. Finally, the Cl equilibrium of the reaction was comprehensively analyzed.